PKM Desain dan Konsultasi Rumah Sehat di Desa Mekarwangi, Banten - Muhammar Khamdevi; Andrey Caesar Effendi; Danang Harito Wibowo (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2020)
The houses in Kampung Cilegong, Mekarwangi Village are still far from the standard of Healthy Homes. Although some were built by artisans with the knowledge of "copy-paste" from cluster housing, there were also some that were built by local governments and offices. A healthy home is a well-designed house, especially looking at the local climate context. Natural lighting and air are the main requirements in designing a healthy home. Therefore, the Architecture Study Program at Matana University tries to carry out PKM activities in the form of training, consultation, and mentoring of several houses in Kampung Cilegong. It is hoped that residents of Kampung Cilegong and the people of Mekarwangi Village will be exposed to the knowledge of the Healthy House and obtain design solutions to set an example. This activity involved students of the 2018 class at Matana University and was integrated with the Building Physics course and the Interior Design Studio. The method of implementation is carried out following the design method. The results of the activity showed a positive response and added insight by the community.